TINJAUAN YURIDIS TERHADAP PERDAGANGAN SAHAM TANPA WARKAT (SCRIPLESS TRADING) DI PASAR MODAL DALAM HUKUM PEMBUKTIAN - Bayu Syafandi Tosmar; Hayatul Ismi; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
In the capital market, securities or shares are the object of sale. Advances in information technology have brought changes in the capital market industry, namely the abandonment of a manual trading system with a computerized electronic-based trading system without the delivery of physical certificates or shares or known as scripless stock trading, which changes are not in line with the provisions in The Civil Code and Law Number 40 of 2007 on Limited Liability Companies, thus complicating the dispute resolution process, especially in court evidence. The objectives of this thesis are: First, to know the implementation of scripless share trading in the Indonesian capital market, Second, to find out the certification of shares in scripless share trading, Third, to find out the proof of share ownership in scripless share trading disputes in court.This research is a type of research that is normative or what is also called doctrinal legal research, which specifically discusses legal principles. Because in this study the authors use a statutory approach, namely an approach that is carried out by examining all statutory regulations that are related to the problems (legal issues) that are being faced. The data sources used are primary data, secondary data, and tertiary data. Data collection techniques are carried out by conducting literature studies.From the research, there are three main points that can be concluded. First, scripless stock trading is carried out electronically by book-entry on the IDX. To make a transaction, an investor must become a customer in a securities company as an intermediary in the sale and purchase of shares. The traded securities must be collectively stored or deposited in the KSEI storage center and guaranteed to KPEI to process the Depository Receipts issuance.Keywords: Trade – Scripless Trading - Proof